Fluoroquinolones suppress gluconeogenesis by inhibiting fructose 1, 6-bisphosphatase in primary monkey hepatocytes. (June 2020) - Iguchi, Takuma; Goto, Koichi; Watanabe, Kyoko; Hashimoto, Kazuyuki; Suzuki, Takami; Kishino, Hiroyuki; Fujimoto, Kazunori; Mori, Kazuhiko
Abstract: Dysglycemia is one of the most serious adverse events associated with the clinical use of certain fluoroquinolones. The purpose of this study was to investigate the effects of the representative fluoroquinolones moxifloxacin and gatifloxacin on hepatic gluconeogenesis using primary monkey hepatocytes. Glucose production was induced after the cells were incubated for 4 h with 10 mM sodium lactate and 1 mM sodium pyruvate as gluconeogenic substrates. Under these conditions, moxifloxacin and gatifloxacin dose-dependently suppressed gluconeogenesis at concentrations of 100 μM or higher. Transcriptome analysis of rate-limiting enzymes involved in hepatic gluconeogenesis revealed that moxifloxacin and gatifloxacin at a concentration of 1000 μM did not affect the expression of key gluconeogenic enzymes such as phosphoenolpyruvate carboxykinase, glucose 6-phosphatase, and fructose 1, 6-bisphosphatase. Furthermore, metabolome analysis, in vitro glucose production assay using additional gluconeogenic substrates, and fructose 1, 6-bisphosphatase assay using the cell extracts showed that fluoroquinolones enzymatically suppressed hepatic gluconeogenesis by inhibiting fructose 1, 6-bisphosphatase. These inhibitory effects may involve in the clinically relevant dysglycemia associated with fluoroquinolones in human. Highlights: Fluoroquinolones suppressed gluconeogenesis in primary monkey hepatocytes. Fluoroquinolones did not affect the gene expression levels of gluconeogenic enzymes. Fluoroquinolones enzymatically suppressed fructose 1, 6-bisphosphatase.